2018
DOI: 10.1111/2041-210x.12957
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing ensembles of small models for predicting the distribution of species with few occurrences

Abstract: Ensembles of Small Models (ESM) represent a novel strategy for species distribution modelling with few observations. ESMs are built by calibrating many small models and then averaging them into an ensemble model where the small models are weighted by their cross‐validated scores of predictive performance. In a previous paper (Breiner, Guisan, Bergamini, & Nobis, Methods in Ecology and Evolution, 6, 1210–1218, 2015), we reported two major findings. First, ESMs proved largely superior to standard models in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
172
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(172 citation statements)
references
References 37 publications
0
172
0
Order By: Relevance
“…In real applications, it is unlikely that the functional form of the model will exactly match the form of the true species responses. Indeed, the species distribution modelling literature has many examples of different modelling methods performing best in different studies, suggesting that no modelling method consistently outperforms others (Bahn & McGill, 2007;Breiner, Nobis, Bergamini, & Guisan, 2018;Cutler et al, 2007;Elith et al, 2006;Elith & Graham 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In real applications, it is unlikely that the functional form of the model will exactly match the form of the true species responses. Indeed, the species distribution modelling literature has many examples of different modelling methods performing best in different studies, suggesting that no modelling method consistently outperforms others (Bahn & McGill, 2007;Breiner, Nobis, Bergamini, & Guisan, 2018;Cutler et al, 2007;Elith et al, 2006;Elith & Graham 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Araújo & New, 2007; Elith & Graham, 2009; Marmion, Luoto, Heikkinen, & Thuiller, 2009). Because the number of known locations of species presence was limited, we employed the ensemble of small models approach implemented in the “ecospat” R package (Breiner, Guisan, Bergamini, Nobis, & Anderson, 2015; Breiner, Nobis, Bergamini, Guisan, & Isaac, 2018; Di Cola et al, 2017). Ecospat fits bivariate models of presence/(pseudo‐)absence with two predictor variables at a time, creating an ensemble of “small” models weighted by each bivariate model's performance.…”
Section: Methodsmentioning
confidence: 99%
“…We used ecospat v.3.1 and Biomod2 v.3.3‐19 to run Maxent models (specifically the MAXENT.Phillips models, as implemented by Phillips, Anderson, & Schapire, 2006), generalized linear models (GLM), classification tree analysis (CTA, also known as classification and regression trees (CART); Breiman, Friedman, Olshen, & Stone, 1984), and artificial neural networks (ANN; Ripley, 1996). In a recent study comparing 10 different modeling approaches implemented in ecospat and Biomod2, these were shown to be the top performing ones, while keeping computation times manageable (Breiner et al, 2018). We used model tuning to optimize the parameter settings for each model.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the past, it was considered a challenge to model the distribution of rare and endangered species (Elith et al, 2006;Guisan et al, 2006); rare species datasets are mostly characterized by low occurrences, resulting in potentially overfitted models when multiple predictors are included (necessary for describing the species' niches, in particular, for rare specialist species with complex habitat requirements; Lomba et al, 2010). A promising step forward to overcome this obstacle was made by considering model ensembles of small models (ESM) to improve the reliability of habitat models (Breiner, Guisan, Bergamini, & Nobis, 2015;Breiner, Nobis, Bergamini, & Guisan, 2018). Few studies have tested the novel ESM approach (Breiner et al, 2018;Di Febbraro et al, 2017), but hitherto, ESM studies on rare flood meadow species cannot be found in literature.…”
Section: Introductionmentioning
confidence: 99%
“…A promising step forward to overcome this obstacle was made by considering model ensembles of small models (ESM) to improve the reliability of habitat models (Breiner, Guisan, Bergamini, & Nobis, 2015;Breiner, Nobis, Bergamini, & Guisan, 2018). Few studies have tested the novel ESM approach (Breiner et al, 2018;Di Febbraro et al, 2017), but hitherto, ESM studies on rare flood meadow species cannot be found in literature.…”
Section: Introductionmentioning
confidence: 99%